Interaction of Cryoprotectants with Model Membranes with High Cholesterol Content - Dyubko, T. S. (Problems of Cryobiology and Cryomedicine, 2006)
Using the fluorescent probe 4-(N-dimethylaminostyryl)-1-methylpirydinium-N-toluene-sulfonate (DSM) the interaction of cryoprotectants (CPs) of different classes (glycerol, ethylene glycol, dimethylsulfoxide, N, N-dimethyl formamide, 1,2-propane diol) with model membranes formed of egg phosphatidylcholine (FC) and its mixture with cholesterol was studied. High concentration of cholesterol (~45 molar %) was found to promote the appearance of DSM bounding sites with increased hydrophobic properties. It was revealed, that CP influence on synthetic membranes with or without cholesterol was of similar nature, specified only by CP chemical structure and rising with their ability to build into lipid bilayer. It was established that the CP’s interaction efficiency with liposomes depended on CP chemical nature and concentration and was more expressed in the cholesterol presence.